1999
DOI: 10.1093/brain/122.7.1341
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function in primary progressive and transitional progressive multiple sclerosis: A controlled study with MRI correlates

Abstract: The relative rarity of primary progressive (PP) and transitional progressive (TP) multiple sclerosis has meant that little documentation of cognitive function in such patients is currently available. The aim of this study was to investigate the cognitive skills of patients with PP and TP multiple sclerosis relative to matched healthy controls, and to examine the relationship of this impairment to MRI parameters. Sixty-three patients (43 PP, 20 TP) were individually matched with healthy controls, who undertook … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
134
1
7

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 218 publications
(151 citation statements)
references
References 40 publications
9
134
1
7
Order By: Relevance
“…Respecto del perfil de la afectación cognitiva de nuestros pacientes, observamos también lo referido por otros autores en cuanto a mayor compromiso de la memoria verbal, velocidad de procesamiento de la información y fluencia verbal [22][23][24][25][26][27] .…”
Section: Discussionunclassified
“…Respecto del perfil de la afectación cognitiva de nuestros pacientes, observamos también lo referido por otros autores en cuanto a mayor compromiso de la memoria verbal, velocidad de procesamiento de la información y fluencia verbal [22][23][24][25][26][27] .…”
Section: Discussionunclassified
“…7,17,25,26 For each patient, a cognitive impairment index was also computed as previously described. 7 Briefly, the cognitive impairment index 7 is a continuous variable obtained by a grading system applied to each patient's score on every cognitive test, dependent on the number of SDs below the mean normative value. These grades are then summed up across all variables to give an overall measure of cognitive dysfunction for each patient (composite cognitive score).…”
Section: Functional Assessmentmentioning
confidence: 99%
“…2 However, another clinical domain that is affected in Յ30% of patients with PPMS is cognition. 7 Previous fMRI studies of cognition in patients with MS with different disease phenotypes have shown that brain plasticity might have a role in maintaining a normal level of function. [8][9][10][11][12][13] However, the fMRI correlates of cognitive network dysfunction in patients with PPMS have not been investigated yet.…”
mentioning
confidence: 99%
“…Most studies reveal that patients with MS are impaired in their ability to explicitly learn and subsequently recall new material, regardless of whether the material is verbal or visual (Amato et al 1995;Beatty et al 1989;Camp et al 1999;Grafman et al 1991;Minden 1990;Rao et al 1984;Ryan et al 1996). Two lines of research have been particularly influential in this regard.…”
Section: Comparison With Msmentioning
confidence: 99%